Infeksi Nematoda Usus pada Petani di Kabupaten Sukoharjo Jawa Tengah dan Faktor yang Mempengaruhinya - Anggraeni Sih Prabandari; Ajeng Novita Sari; Ardita Ferlinda Ahtamagara (Indonesian Journal on Medical Science, 2023)
Farmers are a high-risk group infected with intestinal nematode worms due to close contact with soil which is the medium of development of worm eggs into infective stages. Intestinal nematode infection is associated with clean and healthy living behaviors and knowledge of helminthiasis. This study aims to determine the prevalence of worms in farmers in Wonorejo Village, Polokarto Sukoharjo District, Central Java. This type of study is observational with a cross sectional approach. The identification of intestinal nematodes was carried out by formol ether sedimentation method using fecal samples taken from 31 farmers. The relationship between clean and healthy living behavior and knowledge of worms was analyzed using the Chi square test based on the questionnaire given. Based on the results of the study, the prevalence of intestinal nematode infection was 3.33% (1/31) with hookworm identified species. There was no association between clean and healthy living behavior against intestinal nematode infection in farmers (pvalue 0.93 > 0.05), as well as the level of knowledge about worms (pvalue 0.634 > 0.05).